(untitled) (Psychology Travelogs, 2025)
The article carries out a theoretical analysis of scientific sources regarding the definition of the essence and meaning of the terms "interethnic communication", "tolerance", their characteristics by representatives of the scientific community.It has been established that these questions are in the field of view of representatives of various sciences and their relevance is confirmed by time, intercultural processes and the development of society. The authors of the article note that interethnic communication is a structural component of interethnic interaction. By interethnic communication, scientists understand forms of social interaction and information exchange between representatives of different ethnic groups,which is characterized by processes of communication, mutual understanding, interpretation of cultural meanings and coordination of behavioral norms of representatives of different ethnic groups. It is noted that the term "tolerance" has a long history. The views of scientists differ regarding the definition of its content. So, according to some scientists, this scientific category acts as an individual trait of a person; others define it as a social position and attitude towards another person; the third - as a social norm. The authors of the study adhere to a position in which tolerance, as a component of interethnic communication, acts not only as a valuable characteristic of an individual as a representative of a certain nation, but also as a social norm of a certain society, which ensures the rights of citizens of this state, treats with respect their views, religious preferences, cultural traditions and national belonging. It is noted that the issue of tolerance is enshrined in normative documents, where the principle of tolerance is reflected through intercultural environment and interethnic interaction.Attention is focused on the fact that the indicators of a person’s tolerance characteristics determined by scientists are important, as an element of his intercultural competence. It has been established that tolerance is a fundamental basis for effective interethnic communication in an intercultural society.Thanks to it, it is possible to establish mutual understanding between the participants of interethnic interaction, avoid conflicts, relieve tension between different ethnic representatives, and establish partnership relations.